2016
DOI: 10.1589/jpts.28.450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different running distances on muscle and lymphocyte DNA damage in amateur marathon runners

Abstract: [Purpose] The aim of this study was to investigate the impact of different marathon running distances (10 km, 21 km, and 42.195 km) on muscle and lymphocyte DNA damage in amateur marathon runners. [Subjects and Methods] Thirty male amateur runners were randomly assigned to 10 km, 21 km, and 42 km groups, with 10 subjects in each group. Blood samples were collected before and after the races and on the 3rd day of recovery to examine levels of muscle damage (creatine kinase and lactate dehydrogenase) and lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Numerous studies included heterogeneous groups of participants: trained or untrained, young or old, sport-specific volunteers (such as swimmers, rowers, and runners), physically active and sedentary participants, and a few studies compared men and women. Furthermore, three studies [38][39][40] used more than one parameter to quantify DNA damage. Finally, some studies measured DNA damage at only one time-point (TP), while other studies included multiple post-exercise measures of DNA damage following exercise.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies included heterogeneous groups of participants: trained or untrained, young or old, sport-specific volunteers (such as swimmers, rowers, and runners), physically active and sedentary participants, and a few studies compared men and women. Furthermore, three studies [38][39][40] used more than one parameter to quantify DNA damage. Finally, some studies measured DNA damage at only one time-point (TP), while other studies included multiple post-exercise measures of DNA damage following exercise.…”
Section: Data Extractionmentioning
confidence: 99%
“…Three studies included groups of untrained and trained subjects [36,39,54]; one study [55] used rowers and physical education students, while another [56] used swimmers and runners. Finally, two studies used volunteers participating in multiple running distances [40,49].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ryu et al found that CK and LDH concentrations were increased with increasing marathon distance (10, 20, and 42.2 km). 18 Our findings that CK and LDH concentrations did not recover to at-rest levels by 6 days of recovery after a triathlon race indicates that recovery is delayed following longer exercise. Thus, these athletes require more than 6 days for recovery after a triathlon race.…”
Section: Discussionmentioning
confidence: 66%
“…17 Study results on marathon, which involves longdistance high-intensity aerobic exercise similar to triathlon, showed that exercise distance and time were proportional to oxidative stress and DNA damage from exercise. 18 However, studies on the effects of oxidative stress on DNA damage and those of the event and distance in triathlon on the antioxidant system are still lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation